Inhibition of HER3 activation and tumor growth with a human antibody binding to a conserved epitope formed by domain III and IV. Issue 5 (4th July 2017) - Schmitt, Lisa C.; Rau, Alexander; Seifert, Oliver; Honer, Jonas; Hutt, Meike; Schmid, Simone; Zantow, Jonas; Hust, Michael; Dübel, Stefan; Olayioye, Monilola A.; Kontermann, Roland E.
ABSTRACT: Human epidermal growth factor receptor 3 (HER3, also known as ErbB3) has emerged as relevant target for antibody-mediated tumor therapy. Here, we describe a novel human antibody, IgG 3–43, recognizing a unique epitope formed by domain III and parts of domain IV of the extracellular region of HER3, conserved between HER3 and mouse ErbB3. An affinity of 11 nM was determined for the monovalent interaction. In the IgG format, the antibody bound recombinant bivalent HER3 with subnanomolar affinity (K D = 220 pM) and HER3-expressing tumor cells with EC50 values in the low picomolar range (27 - 83 pM). The antibody competed with binding of heregulin to HER3-expressing cells, efficiently inhibited phosphorylation of HER3 as well as downstream signaling, and induced receptor internalization and degradation. Furthermore, IgG 3–43 inhibited heregulin-dependent proliferation of several HER3-positive cancer cell lines and heregulin-independent colony formation of HER2-overexpressing tumor cell lines. Importantly, inhibition of tumor growth and prolonged survival was demonstrated in a FaDu xenograft tumor model in SCID mice. These findings demonstrate that by binding to the membrane-proximal domains III and IV involved in ligand binding and receptor dimerization, IgG 3–43 efficiently inhibits activation of HER3, thereby blocking tumor cell growth both in vitro and in vivo.